The efficiency of short-term crop rotations with different sunflower saturation - Zinaida Dehtiarova; Mykola Shevchenko; Yurii Dehtiarov; Victor Budyonny (Наукові горизонти)
The study aimed to determine short-term crop rotations’ economic and energy efficiency with varying sunflower saturation. The economic and energy efficiency of crop rotations saturated with sunflower under the conditions of the Left-Bank ForestSteppe region of Ukraine was calculated using technological maps and prices as of 2024. The study employed the following methods: bibliometric analysis – a review of other researchers’ findings on the economic and energy efficiency of sunflower cultivation; grouping – an assessment of the economic and energy effects of varying sunflower saturation in crop rotations; and monographic – the generalisation of the results. The optimum sunflower share in crop rotations was found to be 20% and 40%, at which the production cost remained consistently high at 1,218.0-1,240.8 USD/t. Increasing the sunflower share to 60% led to a decline in the production cost, not only for other crops but also for the sunflower itself. This negatively impacted overall price stability, reducing crop competitiveness and the economic efficiency of crop rotations. Winter rye exhibited the lowest production costs among all crops, regardless of the crop rotation, at 268.9- 321.1 USD/ha. The production costs of soybeans and winter wheat remained stable irrespective of sunflower share, at 413.5 USD and 553.7 USD, respectively, indicating their adaptability. A 20% sunflower share in the crop rotation exhibited the highest energy intensity at 63,348 MJ/ha, while a 60% saturation slightly reduced this figure to 63,279 MJ/ha. However, the 60% sunflower saturation resulted in lower energy consumption compared to other crop rotation options, at 30,293 MJ. These findings indicate the high efficiency of crop rotations with a 60% sunflower share, as evidenced by the energy efficiency ratio of 2.65. As a result of implementing the optimised crop rotation system across 78.9 hectares, sunflower seed yields increased by 0.16 t/ha compared to traditional practices. This improvement led to an additional 1,046 UAH/ha in net profit and a 25.6% increase in production profitability